1991
DOI: 10.1139/z91-005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies of the in vitro chitin and cuticle secretions in the wing pads of Locusta

Abstract: CASSIER, P., and PAPILLON, M. 1991. Ultrastructural studies of the in vitro chitin and cuticle secretions in the wing pads of Locusta. Can. J . Zool. 69: [29][30][31][32][33][34][35][36][37][38].Cuticle deposition and chitin synthesis in the wing pads of 1-day-old fifth-instar larvae of Locusta were stimulated in vitro by 20-hydroxyecdysone and makisterone A. Stimulation was dose-dependent from 2 X lop7 to 2 X lop5 M. The response appeared after a 36-to 48-h lag period characterized by inhibition of the postec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Among them are the phyto‐derived from Meliaceae family, including A. indica (neem)—which has azadirachtin as main active principle. Studies on insects control using this product have demonstrated its effect on the oviposition and fecundity of individuals exposed to it, with consequent interference in the reproduction (Copping and Menn,2000; Isman,1997).…”
Section: Discussionmentioning
confidence: 99%
“…Among them are the phyto‐derived from Meliaceae family, including A. indica (neem)—which has azadirachtin as main active principle. Studies on insects control using this product have demonstrated its effect on the oviposition and fecundity of individuals exposed to it, with consequent interference in the reproduction (Copping and Menn,2000; Isman,1997).…”
Section: Discussionmentioning
confidence: 99%
“…Essa substância, não necessariamente, age matando diretamente o inseto, como a maioria dos inseticidas; atua sobre a reprodução e crescimento ou como toxina direta (ROY;SARAF, 2006). Ao que se sabe, um dos mecanismos de ação mais comum da azadiractina é por meio da inibição da síntese de quitina necessária para o desenvolvimento dos insetos (CASSIER;PAPILLON, 1991).…”
Section: Discussionunclassified